Power Markets and Risk Management Modeling - Paholok, Igor; Málek, Jiří, 1953-; Kodera, Jan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2014)
The main target of this thesis is to summarize and explain the specifics of power markets and test application of models, which might be used especially in risk management area. Thesis starts with definition of market subjects, typology of traded contracts and description of market development with focus on Czech Republic. Thesis continues with development of theoretical concepts of short term/spot electricity markets and potential link between spot and forward electricity markets. After deriving of those microeconomic fundamental models we continue with stochastic models (Jump Diffusion Mean Reverting process and Extreme Value Theory) in order to depict patterns of spot and forward power contracts price volatility. Last chapter deals with credit risk specifics of power trading and develops model (using concept known as Credit Value Adjustment) to compare economic efficiency of OTC and exchange power trading. Developed and described models are tested on selected power markets, again with focus on Czech power market data set.
Vedoucí práce: Jiří Málek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations